Стратегічне планування як інструмент забезпечення економічної безпеки в умовах глобальних змін - Мізін, Д. С.; Турчин, О. А. (ХНУРЕ, 2025)
This article emphasizes the importance of strategic planning in maintaining economic stability amidst global changes. It highlights the need for active economic management to safeguard national interests and adapt to new challenges, such as financial crises, geopolitical conflicts, and climate change. The article discusses the role of tools like SWOT analysis to assess risks and suggests diversifying economic risks to enhance resilience. Furthermore, it underscores the significance of international cooperation and forming strategic alliances to mitigate global uncertainties. Ultimately, effective strategic planning, grounded in risk management and adaptability, is vital for long-term economic growth and stability.
Keywords: стратегічне планування; економічна безпека